Pengaruh Penggunaan Media Permainan Ular Tangga terhadap Minat Belajar PJOK Siswa Kelas IV Sekolah Dasar - Hana Fairuz Syifa; Bayu Thomi Rizal (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Lack of various learning medium is one of the problems in education, particularly for students, since it causes them to get disinterested and not participate as much in class activitiesThere is no text provided. The objective of this study is to assess the impact of using the game of snakes and ladders as an educational tool on primary school kids' interest in physical education subjects among elementary school students The study's quantitative technique employed a posttest-only control design, sometimes known as a quasi-experimental design. The research population consisted of 96 students that were enrolled in the fourth grade at SDN Susukan 09 Pagi. Class IV-C was designated as the experimental group, whereas class IV-B was assigned as the control group, employing a purposive sampling technique. The posttest questionnaire was employed to collect data for the purpose of comparing the levels of interest in learning between the two groups. Data analysis was conducted using the SPSS 25 software, employing a t-test. Given a significance value of < 0.05 and a t-test result of 0.000, we accepted the alternative hypothesis (Ha) and rejected the null hypothesis (H0). Therefore, it can be concluded that fourth-grade PJOK students at SDN Susukan 09 Pagi exhibit a high level of enthusiasm for learning as a result of utilizing the snakes and ladders gaming medium.